Genetic events in the progression of adenoid cystic carcinoma of the breast to high-grade triple-negative breast cancer - Fusco, Nicola (Mod Pathol, 2016)
Adenoid cystic carcinoma of the breast is a rare histologic type of triple-negative breast cancer with an indolent clinical behavior, often driven by the MYB-NFIB fusion gene. Here we sought to define the repertoire of somatic genetic alterations in two adenoid cystic carcinomas associated with high-grade triple-negative breast cancer. The different components of each case were subjected to copy number profiling and massively parallel sequencing targeting all exons and selected regulatory and intronic regions of 488 genes. Reverse transcription PCR and fluorescence in situ hybridization were employed to investigate the presence of the MYB-NFIB translocation. The MYB-NFIB fusion gene was detected in both adenoid cystic carcinomas and their associated high-grade triple-negative breast cancer components. Whilst the distinct components of both cases displayed similar patterns of gene copy number alterations, massively parallel sequencing analysis revealed intra-tumor genetic heterogeneity. In case 1, progression from the trabecular adenoid cystic carcinoma to the high-grade triple-negative breast cancer was found to involve clonal shifts with enrichment of mutations affecting EP300, NOTCH1, ERBB2 and FGFR1 in the high-grade triple-negative breast cancer. In case 2, a clonal KMT2C mutation was present in the cribriform adenoid cystic carcinoma, solid adenoid cystic carcinoma and high-grade triple-negative breast cancer components, whereas a mutation affecting MYB was present only in the solid and high-grade triple-negative breast cancer areas and additional three mutations targeting STAG2, KDM6A and CDK12 were restricted to the high-grade triple-negative breast cancer. In conclusion, adenoid cystic carcinomas of the breast with high-grade transformation are underpinned by MYB-NFIB fusion gene, and, akin to other forms of cancer, may be constituted by a mosaic of cancer cell clones at diagnosis. The progression from adenoid cystic carcinoma to high-grade triple-negative breast cancer of no special type may involve the selection of neoplastic clones and/ or the acquisition of additional genetic alterations.